2009
DOI: 10.2298/eka0983089k
|View full text |Cite
|
Sign up to set email alerts
|

A strategic model for measuring intellectual capital in Serbian industrial enterprises

Abstract: Measuring intellectual capital contributes to organizational success and brings managerial, cultural and organizational changes. In analyzing the relevant literature on intellectual capital (IC), it emerges that the benefits of IC measuring and reporting have been linked to value creation. In order to provide a deeper understanding of the character and role of IC and adequate IC indicators, the main aim of this study is to propose a strategic model for measuring intellectual capital in Serbian industrial enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
10
2
Order By: Relevance
“…2, relational indicators are considered most useful, while structural indicators are considered least useful. This differs from the results of the research by Kontic andCabrilo (2009), andMiller et al (1999), which showed that human capital indicators were regarded as the most useful. Having said that, the latter study's results were similar to ours in a way that relational and human capital indicators were perceived to be more useful than structural capital indicators.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…2, relational indicators are considered most useful, while structural indicators are considered least useful. This differs from the results of the research by Kontic andCabrilo (2009), andMiller et al (1999), which showed that human capital indicators were regarded as the most useful. Having said that, the latter study's results were similar to ours in a way that relational and human capital indicators were perceived to be more useful than structural capital indicators.…”
Section: Resultscontrasting
confidence: 94%
“…The highest rated items are connected to communication and exchange of ideas, adjustment to market changes, product quality, customer satisfaction, IT, and relationship with partners. After interviewing 109 higher managers from 13 large and medium sized companies belonging to different sectors in Serbia, Kontic and Cabrilo (2009) found that human indicators are more important than relational and structural IC indicators. The study revealed that the main drivers of human capital are motivation, experience, and efficiency.…”
Section: Knowledge-based Bioeconomy: the Use Of Intellectual Capital mentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the Balanced Scorecard is to give managers a comprehensive view of the business and allow them to focus on critical areas. The concept of the balance scorercard is based on the assumption that the efficient use of investment capital is no longer the key determinant of competitive advantage, and that soft factors such as intellectual capital and knowledge creation are increasingly becoming more important [49].…”
Section: Models To Measure Intellectual Capitalmentioning
confidence: 99%
“…In some cases organizational changes can be riskier than strategic change. Fortunately, the organizational restructuring have been successful in 84.82% observed firms (Kontic, 2007). …”
Section: Internal Factorsmentioning
confidence: 99%